Write the sum of the coefficients in the expansion of

Question:

Write the sum of the coefficients in the expansion of $\left(1-3 x+x^{2}\right)^{111}$.

Solution:

To find the sum of coefficients, we plug 1 for each variable then, we get the sum of coefficients of the given expression.

$\therefore$ Sum of coefficient $=\left(1-3 x+x^{2}\right)^{111}$

$=\left(1-3 \times 1+1^{2}\right)^{111}$

$=(1-3+1)^{111}$

$=(1-3+1)^{111}$

$=(-1)^{111}$

$=-1$

Leave a comment

Close
faculty

Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now